Engineering nanostructures of PGM-free oxygen-reduction catalysts using metal-organic frameworks. (January 2017) - Zhang, Hanguang; Osgood, Hannah; Xie, Xiaohong; Shao, Yuyan; Wu, Gang
Abstract: Oxygen reduction reaction (ORR) is one of the essential electrochemical reactions for the energy conversion and storage devices such as fuel cells and metal-air batteries. However, a large amount of Pt is required for catalyzing the kinetically sluggish ORR at the air cathode, therefore greatly limiting their large scale implementation. Development of high-performance platinum group-metal (PGM)-free ORR catalysts has been a long-term goal for these clean energy technologies. However, current PGM-free catalysts are still significantly suffering from insufficient activity and limited durability especially in more challenging acidic media, such as proton exchange membrane (PEM) fuel cells. Recently, metal-organic frameworks (MOFs), constructed from bridging metal ions and ligands, have emerged as a new type of attractive precursors for the synthesis of PGM-free catalysts, which has led to encouraging performance improvement. Compared to other catalyst precursors, MOFs have well-defined crystal structure with readily tunable chemistry and contain all required elements ( e.g ., carbon, nitrogen, and metal). Here, we provide an account of recent innovative PGM-free catalyst design and synthesis derived from the unique MOF precursors with special emphasis on engineering nanostructure and morphology of catalysts. We aim to provide new insights into the design and synthesis of advanced PGM-free catalysts with increased density of active sites and controlled bonding in 3D frame network. In addition, we also discuss the possibility to use the well-defined MOF precursors for building up model systems to elucidate the structure-property correlations and the nature of active sites. Graphical abstract: Highlights: Highlight the advantages of metal organic framework (MOF) precursors for PGM-free catalyst synthesis. Provide a comprehensive overview of designing MOF precursors. Focus on engineering catalyst nanostructures with optimal electrocatalytic properties. Elucidate synthesis-structure-activity correlations for MOF-derived catalysts. Outline the future catalyst technologies by designing optimal MOF precursors.